Upaya Meningkatkan Proses Pembelajaran PAK Melalui Strategi Inkuiri pada Siswa Kelas X di SMK Elpida - Dominggus Umbu Dingu; Yublina Tefa; Yanto Tefa (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The results of initial observations in class X of SMK Elpida Informatika showed that students' process skills were less trained. Although in the learning process the teacher had tried to apply inquiry learning, in its implementation the students depended on each other in their groups. In addition, the average PAK test score for class X had not met the KKM. The application of the inquiry strategy approach in the learning process will be centered on students who emphasize the ability to search for themselves or find themselves. This study aims to determine the improvement in student learning outcomes by applying process skills and discussions between group members can make students active in their learning activities which results in maximum results achieved. This study is a classroom action research carried out in three cycles consisting of planning, implementation, observation, and reflection. The subjects of the study were students of class X of SMK Elpida Informatika. Data collection was carried out by observation. Based on the analysis of the research data, the average cognitive results of students in cycle I were 51.07, cycle II 60.5 and increased to 85.71 in cycle III. The affective learning outcomes of students obtained in cycle I were 85%, cycle II 95% and cycle III increased to 100%. Psychomotor learning outcomes in the form of process skills increased with the average learning outcomes of students obtained in cycles I, II and III respectively being 61.34; 84.10; and 93.4.